PELUANG USAHA MAKANAN Di ERA PANDEMI Covid 19 STUDI KASUS RUMAH MAKAN PAMENAN DIKECAMATAN RAWALUMBU - Eriandi Eriandi (Institut Bisnis Muhammadiyah Bekasi, 2022)
Aside from the serious impact on health, Covid-19 Pandemic also weakens the national economy. Various industrial sectors, including the culinary business, experienced a decrease in turnover rate, and not a few closed their businesses. However, during the Covid-19 pandemic, there are still opportunities to open businesses for small entrepreneurs engaged in the culinary sector. In order to be able to compete and acquire consumers amid declining purchasing power then the entrepreneurs must be innovative, including using an online system in their sales strategy. This is implemented to comply with regulations to always maintain distance and at the same time break the chain of spreading COVID-19. Research on business opportunities in the culinary sector during the Covid 19 pandemic was conducted in Rawalumbu District by taking the case of the Dapoer Pamenan Restaurant, Rawalumbu District. This research uses a the descriptive qualitative method by using a SWOT analysis to find out the various strengths, weaknesses, opportunities, and threats that the culinary business has during a pandemic. The result of this research shows that the strategy that can be carried out by the culinary business is product and service diversification. The culinary business must be able to gain consumer trust through safe products, healthy and hygienic, implement the health protocol, maximize online marketing, fulfill the demands of take-away and delivery orders, making diversified product innovations in the form of healthy food and frozen food, and also optimize the quality of the products. The target outcome of this research is to identify the factors of strengths, weaknesses, opportunities, and threats that will be faced by the culinary business entrepreneurs in the Rawalumbu sub-district and also to decide the suitable strategy applied to adapt to the new normal. In the long term, it is hoped that the results of this study will contribute to the development of business strategies to deal with emergency and uncertain situations.